SARS-CoV-2 a public health emergency: challenges in vaccination in Indian setup - Dakshinamurthy, Senkadhirdasan; Boratne, Abhijit V.; Kanagat, Sadhvika (International Journal Of Community Medicine And Public Health, 2021)
WHO is working in collaboration with scientists, business, and global health organizations to fasten the pandemic response. India has approved two vaccines, Covishield and Covaxin for emergency use to fight COVID-19 pandemic in the country. Even when vaccinations are provided free of cost in PHCs, some social stigma always present in communities which make hardest-to-reach remote rural areas. Enhancing access to vaccination services, provider-based interventions and increasing community demand are some areas of concern. In spite of all recommendations, certain challenges like safety of vaccines, human rights and law, trust and prevention of distrust etc. remain to be solved before planning to introduce a new vaccine in the public health system. In the first phase of the vaccination drive, frontline workers nearly from both government and private sector will get vaccinated. These include cleaners, police and paramilitary, home guards, disaster management volunteers and other jawans in civil defence, and revenue officials associated with containment and surveillance. In the second and third stage, those above 45 years of age with comorbidities and then without comorbidities will be vaccinated. Later people in age group of more than 18 years will get vaccine.